A Case of Acute Motor Sensory Axonal Neuropathy: A Variant of Guillain-Barré Syndrome, with Possible Syndrome of Irreversible Lithium-Effectuated Neurotoxicity - David Y. Liu; Jessica R. Hollenbach; Jason A. Gregorin; Jonathan H. Wynbrandt (Case Reports in Medicine)
Acute Motor Sensory Axonal Neuropathy (AMSAN) is a rare and severe variant of Guillain-Barré syndrome (GBS) that has a prolonged recovery course. GBS is often suspected due to ascending muscle weakness, sensation difficulties, respiratory compromise, and antecedent diarrhea. The diagnosis of GBS is supported by cerebrospinal fluid analysis showing albuminocytologic dissociation. Electromyogram and nerve conduction study confirm the diagnosis and allow for further classification by variant. Treatment involves either IV immune globulins or plasmapheresis, and patients typically recover. However, depending on the variant and severity, patients may ultimately require prolonged mechanical ventilation with tracheostomy. In these cases, they may continue to have persistent muscle and sensation abnormalities requiring long-term care. We present a unique case of a 38-year-old female patient with decade-long use of lithium for bipolar disorder that presented with acute lithium toxicity. Though she was ultimately diagnosed with AMSAN, the Syndrome of Irreversible Lithium-Effectuated Neurotoxicity (SILENT) may have also contributed to her persistent neurological sequelae.